On the Challenges of Measuring Energetic Particles in the Inner Belt: A Geant4 Simulation of an Energetic Particle Detector Instrument, REPTile‐2. Issue 4 (11th April 2022) - Khoo, L.‐Y.; Li, X.; Selesnick, R. S.; Schiller, Q.; Zhang, K.; Zhao, H.; Hogan, B.; Cantilina, J. T.; Sims, A.; Bauch, E.; Valade, T.; Boyajian, S.; et al.
Abstract: Following the retirement of the community supported Van Allen Probes mission, the quest for high‐quality energetic particle measurements in the radiation belts is likely to be taken on by smaller spacecraft like CubeSats in the foreseeable future. Here we introduce the Relativistic Electron Proton Telescope integrated little experiment‐2 (REPTile‐2), a miniaturized (∼1.5 U) solid‐state charged particle telescope that aims to undertake this challenging task. It incorporates detailed pulse‐height analysis to enable 60 electron channels and 60 proton channels and includes anticoincidence detectors to minimize unwanted background contamination. This paper presents a description of the REPTile‐2 design and emphasizes the importance of extensive Geant4‐based analysis to inform the design of a new energetic particle detector and characterize the instrument response. Our analysis shows that REPTile‐2 can measure ∼0.3–∼4 MeV electrons and ∼6.7–35 MeV protons with energy resolution (∆E/E) of 7%–38% for electrons and 1.5%–5% for protons. Results from a Sr‐90/Y‐90 radioactive source test have verified the instrument performance and the validity of the Geant4 simulations. These energetic particle measurements will enable a new scientific understanding of the inner radiation belt, where unwanted contamination from the unforgiving penetration of highly energetic protons (tens of MeV to GeV) is common, and provide detailed quantification of the inner belt electrons and protons in the low‐Earth orbit that is crucial for space weather modeling. Key Points: REPTile‐2 is a miniaturized particle telescope measuring electrons and protons with fine energy resolution and minimal contamination This study highlights the key role of anticoincidence detectors in reducing contamination and improving measurement quality Detailed Geant4 simulations have proved to be instrumental in characterizing instrument response and potential contamination sources